CPD Students from the International Bureau of Management Reacting to Long-Distance Learning - Esmeralda, Angel (MID Publisher International, 2024)
This study explores the varied responses of CPD (Continuing Professional Development) students from the International Bureau of Management (IBM), particularly those enrolled at the Asian Ministry of De Instituto, toward long-distance learning. The researchfocuses on evaluating students’ experiences with remote education, with particular attention to demographic variables such as age and gender. A descriptive research design was employed, and statistical tools, including the t-test and F-test, were utilizedto assess the significance of differences among variables. Percentages were also used to illustrate comparative data distributions. The sample consisted primarily of male students, with 46 male and 4 female respondents. The findings contribute to a broader understanding of how distance education is perceived by CPD students, offering insights that may inform future instructional strategies and policy decisions.